SHARING THE GOSPEL: Jesus in the Speeches of Acts - W. Stenschke, Christoph (Asian Horizons, 2011)
Many Christians are fascinated by the early Church. For many, particularly those from the various restoration movements (like the Baptist tradition), the New Testament descriptions of the early Church serve as blueprints for the life and ministry of the Church in all ages. If the early Church were emulated as closely as possible, many issues would be resolved! Of particular interest are the ways in which these exemplary Christians spread the good news of Jesus.1 As there are only a few references to evangelism in the letters of the New Testament, the most obvious place to search for answers is the book of Acts, in particular the missionary speeches. How did the early Christians speak of Jesus in their evangelism? However, looking for Jesus in the speeches of Acts raises several issues.